2018
DOI: 10.1007/s12035-018-1297-0
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Lin28 Expression Impairs Neurite Outgrowth and Cognitive Function in the Developing Mouse Neocortex

Abstract: Many neurodevelopmental disorders feature learning and memory difficulties. Regulation of neurite outgrowth during development is critical for neural plasticity and memory function. Here, we show a novel regulator of neurite outgrowth during cortical neurogenesis, Lin28, which is an RNA-binding protein. Persistent Lin28 upregulation by in utero electroporation at E14.5 resulted in neurite underdevelopment during cortical neurogenesis. We also showed that Lin28-overexpressing cells had an attenuated response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Lin28 is found in the cytoplasm and cytoplasmic bodies such as processing bodies and stress granules, and partially in the nucleus (Kawahara et al, 2012). While Lin28 is expressed in cell-renewing cells to promote cell proliferation, let7 is absent in stem cells (Rehfeld et al, 2015;Jang et al, 2019). Lin28B can be found in progenitor cells and the cerebral cortex whereas both Lin28A and Lin28B are expressed in neural progenitor cells expressing nestin and Pax6 in the ventricular and SVZ (Hennchen et al, 2015).…”
Section: Lin28mentioning
confidence: 99%
“…Lin28 is found in the cytoplasm and cytoplasmic bodies such as processing bodies and stress granules, and partially in the nucleus (Kawahara et al, 2012). While Lin28 is expressed in cell-renewing cells to promote cell proliferation, let7 is absent in stem cells (Rehfeld et al, 2015;Jang et al, 2019). Lin28B can be found in progenitor cells and the cerebral cortex whereas both Lin28A and Lin28B are expressed in neural progenitor cells expressing nestin and Pax6 in the ventricular and SVZ (Hennchen et al, 2015).…”
Section: Lin28mentioning
confidence: 99%
“…These mRNA targets are mostly involved with the Igf2–mTOR signaling pathway that drives progenitor proliferation ( Hentges et al, 2001 ). Other studies have directly linked Lin28a function with translational regulation and cell division by showing that Lin28a silencing decreases the levels of its targets Hmga2 and Igf1r , whereas Lin28a OE upregulates Hmga2 and Igf2 in mouse primary cultures of electroporated cortical neurons ( Bhuiyan et al, 2013 ; Jang et al, 2019 ). Polysome profiling analysis of Lin28a/b KO embryonic neocortices indicated that transcripts associated with translation, ribosome biogenesis, mTOR pathway, and cell cycle are decreased, whereas transcripts involved with neuronal differentiation are significantly upregulated in double mutants.…”
Section: Post-transcriptional Regulation Mrnas Poised For Translation and Rna-binding Proteinsmentioning
confidence: 99%
“…Not surprisingly, various RBPs, including Arpp21, Rbfox1, Lin28, Pumilio2, Staufen2, Elavl4, Ythdf, and FMRP, regulate the expression of mRNAs involved in synaptic transmission and neurite outgrowth. This directly serves as a link between RBPs, neuronal dysfunction, and occurrence of neurodevelopmental disorders ( Rehfeld et al, 2018 ; Vuong et al, 2018 ; Jang et al, 2019 ; Bowles et al, 2021 ; Schieweck et al, 2021 ; Sena et al, 2021 ; Worpenberg et al, 2021 ).…”
Section: Establishment Of the Unique Layered Structure Of The Neocortexmentioning
confidence: 99%
“…As induced pluripotent stem cells (iPSCs) and new transgenic mouse lines become more readily available, it will be interesting to see whether and how these interactions occur in a stem cell context and within specific cell types of the brain and what effect they may have on development, neuronal function, and synaptic plasticity. Multiple papers have provided evidence regarding the importance of NF-κB in a variety of forms of neuronal plasticity and synapse development, however, it is only relatively recently that a link between the Lin28/let-7 pathway and neuronal plasticity has been observed [41,46,126,127]. As the interactions between NF-κB and the Lin28/let-7 pathway become more apparent, future research can be aimed at elucidating how these interactions impact the most critical features of brain development, neuroplastic function, and neural disorders.…”
Section: Conclusion Ongoing Questions Future Directionsmentioning
confidence: 99%